Enhancing the work engagement of frontline nurses during the COVID-19 pandemic: the mediating role of affective commitment and perceived organizational support - Yawei Shan; Xuemei Zhou; Zhiyi Zhang; Weijia Chen; Ru Chen (BMC Nursing, 2023)
Abstract Background Overload and anxiety were common phenomena among frontline nurses during the pandemic. Understanding the potential pathway for fostering engagement in high-stress working conditions can provide evidence of targeted intervention to facilitate nurses’ well-being and safety practices. This study aims to investigate the level of nurses’ work engagement during nucleic acid collection tasks in the COVID-19 pandemic and identify its potential antecedents. Methods A cross-sectional design was adopted. A sample of 824 nurses who engaged in nucleic acid collection tasks completed an online self-report questionnaire between 1 March and 31 May 2022. Descriptive and path analyses were utilized to analyse the interrelationships among anxiety, perceived workload, affective commitment, perceived organizational support and work engagement. This study was conducted and reported under the guidelines for Strengthening the Reporting of Observational Studies in Epidemiology. Results The results showed that frontline nurses engaged in such tasks reported high levels of anxiety and task load and low levels of work engagement. Path analysis identified anxiety symptoms, perceived workload, perceived organizational support, and affective commitment as associated with work engagement, and among these factors, perceived organizational support and affective commitment played key roles in mediating the relationship of anxiety, workload and work engagement in high-stress working conditions. Conclusions Affective commitment and perceived organizational support were associated with frontline nurses’ level of work engagement during the COVID-19 pandemic; these two variables might explain how engagement is generated in high-anxiety and high-workload situations. When healthcare organizations give more attention to frontline nurses’ physical and psychological conditions and are able to innovatively motivate affective commitment and facilitate organizational support, nurses’ work engagement in high-level tasks may increase, thus enhancing work safety and personal well-being.